Gracilechinus affinis - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; De, António M.; Martins, Frias; Ávila, Sérgio P. (Zenodo, 2019)
Gracilechinus affinis (Mortensen, 1903) Reports for the Azores: Echinus affinis Mortensen, 1903 — $ Koehler 1909: 229–230, pl. 31, figs. 1–2, 19; Mortensen 1927a: 305–306, fig. 174, 1943a: 83–86, pl. 11, figs. 1–7, pl. 55, figs. 15, 17, 19; Gage et al. 1985: 183–184; Serafy & Fell 1985: 21, fig. 26; Gracilechinus affinis Mortensen, 1903 — Mironov 2014: 123. Type locality: south of Iceland. See: Mortensen (1903: 150–152, pl. 5, figs. 4, 8, pl. 15, figs. 3, 10, pl. 16, figs. 6, 20, pl. 18, figs. 4, 16, 28, pl. 19, fig. 27, pl. 20, figs. 17, 21; 1943a). Occurrence: North Atlantic, from the east coast of the USA, the Denmark Strait and Iceland (Mortensen 1903) south to Rockall Trough (D̂derlein 1906), Galicia (N Spain; Koehler 1921a) and the Azores (Koehler 1909). Depth: 770–2,700 (?5,300) m (Mironov 2014); AZO: 1,482 –2,252 m (Koehler 1909). Habitat: soft bottoms, muddy sand to ooze (Koehler 1909, Gage et al . 1985); possibly an opportunistic scavenger (Gage et al . 1985). Larval stage: planktotrophic (Young & Tyler 1993). Remarks: Gracilechinus affinis is known from the Azores only from Koehler (1909) who reported this species (as Echinus affinis ) among the material collected by Princesse Alice at several stations. This species was the fourth species of the genus Gracilechinus reported from the archipelago at one time. The presence in the Azores of G . acutus and G . elegans were dismissed as unconfirmed and erroneous respectively since the first was based on poorly preserved juveniles (see remarks under G . alexandri ) and the other is likely to be based on misprint by Mortensen (1927a), reducing the presence of this genus in the Azores to just two species. Published as part of Madeira, Patrícia, Kroh, Andreas, Cordeiro, Ricardo, De, António M., Martins, Frias & Ávila, Sérgio P., 2019, The Echinoderm Fauna of the Azores (NE Atlantic Ocean), pp. 1-231 in Zootaxa 4639 (1) on pages 109-110, DOI:10.11646/zootaxa.4639.1, http://zenodo.org/record/3342161